NUMERICAL ANALYSIS OF EFFECTS OF HYDRAULIC GRADIENT ON MASS FLUX OF SALTWATER INTRUSION IN COASTAL AQUIFERS - JAMES A. ADEGOKE; OLATUNDE I. POPOOLA; OLUDOTUN O. FALUY (Journal of Engineering Studies and Research)
Coastal aquifers are distinguished from other aquifers because of saltwater intrusion effects, which cause contamination of groundwater in coastal regions. This study addressed the significance of hydraulic gradient and porosity of the coastal aquifers on contaminant transport of saltwater. Results showed hydraulic gradient of the aquifer has significant impact on the contaminant transport in coastal aquifer. When the hydraulic gradient between freshwater and saltwater is high and directed toward the sea, diffused rate of saltwater into the groundwater would be low. Therefore, hydraulic head of freshwater in coastal aquifer must be maintained at high level to control saltwater intrusion.